Modified variational iteration method for analytical solutions of nonlinear oscillators. Issue 3 (December 2019) - He, Wei; Kong, Hua; Qin, Yan-Mei
The second-order nonlinear oscillators have rich dynamics. We proposed a novel analytical method based on both variational iteration method and Adomian method. The variational iteration method is used to establish an equivalent integral system. So then Adomian polynomials are adopted to linearize the strong nonlinear terms in nonlinear oscillators and analytical solutions are obtained successively.